Strengthening budget institutions in Public Expenditure Management Peer Assisted Learning (PEMPAL) countries Results of the 2013-14 OECD PEMPAL Budget Practices and Procedures Survey - Downes, Ronnie (OECD Publishing, 2017)
This report is the result of a survey conducted in 2013 and finalised in 2014. The survey was based on self-reporting by 33 OECD and 13 PEMPAL countries and involved the participation of OECD and World Bank staff. This report is organised according to 7 main dimensions of the budget process. These 7 dimensions is addressed in greater detail in sections 2 to 8. JEL codes: H11, H50, H60, H70 Keywords: PEMPAL, Fiscal sustainability, MTEF, capital budgeting, budgeting techniques, performance budgeting, budget transparency, budgetary governance